Pengembangan Media Pembelajaran Berbasis Website Google Sites menggunakan Pendekatan Saintifik untuk Melatih Numerasi Siswa pada Materi Hukum Dasar Kimia - A'yuni, Qurrota; Ardhana, Ivan Ashif (Chemistry Education Review (CER), 2024)
In this era of independent learning, students must strengthen their numeracy skills. The purpose of this study is to determine the process of developing web-based learning media google sites using a scientific approach to train student numeracy on basic chemical law material, determine the feasibility of learning media based on the assessment of validators, and determine the responses of teachers and students to the learning media. The research and development (R&D) model used is the ADDIE model (analyze, design, development, implementation, and evaluation). The research instruments used were interview guidelines, validation sheets and questionnaire sheets. Validation was carried out by a team of experts who were chemistry lecturers and chemistry teachers. Limited trial subjects were 29 students of class X MA Al-Ma'arif Plus Tulungagung Skills. The data analysis technique used is descriptive quantitative and descriptive qualitative. The results of this study are to produce a product in the form of google sites website-based learning media using a scientific approach to train student numeracy on basic chemical law material, product feasibility gets an average percentage from a team of experts of 91% with “very valid” criteria, teacher responses obtained an average percentage of 95% with “very valid” criteria and student responses obtained an average percentage of 79% with “feasible” criteria. Thus it can be concluded that the learning media based on the google sites website using a scientific approach is feasible to use as a learning media.